REMEDIASI KEMAMPUAN SISWA MENGGUNAKAN SYSTEMATIC APPROACH TO PROBLEM SOLVING PADA MATERI DINAMIKA ROTASI - Arrizal, Muhammad; Sahala S, Stepanus; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was quasi experimental design with nonequivalent control group design. The effectiveness of systematic approach to problem solving in improving students’ ability to solve the rotational dynamics problem in SMAN 2 Pontianak was investigated. 120 students selected used intact group and randomly, obtained 30 students in XI MIA 3 class as the experimental group was taught by using systematic approach to problem solving and 30 students in XI MIA 2 class as the control group was taught by using formal education method. Essay test questions about rotational dynamics were used for data collection. The results of study reveal the average score of experimental group increased from 32.5 to 68.1 and in control group increased from 35 to 54. T–test was used on this study with the significance of 5%. There were significant differences in problem solving abilities after being remediated using a systematic approach. There are also significant difference between experimental and control groups students’ posttest scores. Systematic approach to problem solving can effectively improve students' ability to solve problems with effect size of 3.04. This study is expected to be used as an alternative learning for students who have difficulty in solving problems especially in physics. Keyword: Systematic approach to problem solving, Students’ Ability, Rotational Dynamics